1989
DOI: 10.1002/ca.980020405
|View full text |Cite
|
Sign up to set email alerts
|

Imaging anatomy of the cranio‐vertebral junction (occipito‐atlanto‐axial joint)

Abstract: The diagnostic value of magnetic resonance imaging (MRI) is directly related to the ability to interpret differences between significant pathology and normal anatomical variations. A multidisciplinary investigation of the cranio-vertebral articulation with CT, MRI, anatomical dissections and sections, 3D reconstruction, and injections of contrast into the joint spaces has demonstrated some of the anatomical structures which can cause differences in CT and MR images. Some of the factors which can contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Grabb et al 25 used T2-weighted MR imaging to directly visualize lesions in the tectorial membrane in 5 pediatric patients who had suffered trauma. Engelman et al 19 also used T1-weighted MR imaging to visualize the tectorial membrane and the other structures of the supraodontoid space. 28 Bloom et al 4 successfully diagnosed injuries to the tectorial membrane using thinsection contiguous axial CT scans to visualize areas of discontinuity in the soft tissues.…”
Section: Imaging Of the Ligamentous Structures Of The Ccjmentioning
confidence: 99%
See 1 more Smart Citation
“…Grabb et al 25 used T2-weighted MR imaging to directly visualize lesions in the tectorial membrane in 5 pediatric patients who had suffered trauma. Engelman et al 19 also used T1-weighted MR imaging to visualize the tectorial membrane and the other structures of the supraodontoid space. 28 Bloom et al 4 successfully diagnosed injuries to the tectorial membrane using thinsection contiguous axial CT scans to visualize areas of discontinuity in the soft tissues.…”
Section: Imaging Of the Ligamentous Structures Of The Ccjmentioning
confidence: 99%
“…Grabb et al 25 successfully demonstrated tears in the apical ligament on T2-weighted images of the CCJ. Engelman et al 19 identified the contents of the supraodontoid space using MR imaging. They successfully identified the apical ligament, as well as the alar ligaments, fat pad, and a venous plexus.…”
Section: Imaging Of the Ligamentous Structures Of The Ccjmentioning
confidence: 99%
“…There is a number of studies in the literature on imaging of normal anatomy and imaging techniques for the transverse, apical, anterior and posterior atlantooccipital ligament [2,[5][6][7][8]15,[19][20][21]. The majority of these studies have been carried out on 1.5T MR units and there is only one study assessing the normal anatomy of accessory atlantoaxial ligament at 3T and its relationship to the ligamentous complex of the CC junction [11].…”
Section: Discussionmentioning
confidence: 99%
“…A knowledge of the anatomy of the supraodontoid space, especially the microdissection scale anatomy, is sparse and fragmentary (Engelman et al, 1989, Tubbs et al, 2000. This space is defined as the small extradural space between the foramen magnum above and the upper surface of the alar ligaments below, that is, above the apex of the dens axis.…”
Section: Introductionmentioning
confidence: 99%
“…No periapical bursa was found as previously reported (Werne, 1957), neither were blood vessels observed within the apical ligament (Heker, 1922). Engelman et al (1989) used MRI T1-weighted imaging studies to investigate the supraodontoid space structures. They visualized the apical ligament, the ''supraodontoid bursa,'' fat pads, anomalies of the dens, ligaments, and flow patterns in the vertebral venous plexus.…”
Section: Introductionmentioning
confidence: 99%